2020
DOI: 10.2478/aoas-2020-0039
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Dairy Cattle Housing Systems on the Concentrations and Emissions of Gaseous Mixtures in Barns Determined by Fourier-Transform Infrared Spectroscopy

Abstract: AbstractThe aim of this study was to determine the concentrations and emissions of greenhouse and odorous gases in different types of dairy cattle housing systems with the use of Fourier-transform infrared (FTIR) spectroscopy. The study was performed in autumn and winter in four types of dairy cattle barns with different process and technical systems (free-stall, deep litter – FS-DL; free-stall, sub-floor manure storage – FS-SFM; free-stall, litter in stalls – FS-LS; tie-stall,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…In general, the level of ammonia emissions measured in this study is comparable to the level reported in the Webb synthesis (30 ± 20 g NH 3 -N d -1 animal place -1 [6], but lower than those recently reported in naturally ventilated buildings (40-60 g NH 3 -N d -1 LU -1 , LU: Livestock Unit [4]; 60-100 g NH 3 -N d -1 LU -1 [7]). In addition to the different measurement methods for gas concentrations and ventilation rates, bedding management practices (e.g., straw added every 2 days, accumulation under the animals for 3 months in Witkowska et al [7]) may explain these contrasting results.…”
Section: Ammonia Emissions Associated With N Excretion In the Barn An...supporting
confidence: 82%
See 1 more Smart Citation
“…In general, the level of ammonia emissions measured in this study is comparable to the level reported in the Webb synthesis (30 ± 20 g NH 3 -N d -1 animal place -1 [6], but lower than those recently reported in naturally ventilated buildings (40-60 g NH 3 -N d -1 LU -1 , LU: Livestock Unit [4]; 60-100 g NH 3 -N d -1 LU -1 [7]). In addition to the different measurement methods for gas concentrations and ventilation rates, bedding management practices (e.g., straw added every 2 days, accumulation under the animals for 3 months in Witkowska et al [7]) may explain these contrasting results.…”
Section: Ammonia Emissions Associated With N Excretion In the Barn An...supporting
confidence: 82%
“…These processes depend on animal behavior and use of space, temperature, moisture content, the carbon (C):N ratio, pH, oxygen level, and the physical structure of the organic substrate. In the literature, conflicting results are reported, as solid manure is described to emit less NH 3 -N than liquid manure at the barn level [3][4][5] or more [6,7]. However, all of these studies were conducted in contrasting environmental conditions, herd sizes, diets, methodological approaches, and manure management practices.…”
Section: Introductionmentioning
confidence: 99%
“…Stress, poor hygiene, temperature fluctuations, high humidity and inadequate ventilation in the barn can compromise immunity and increase susceptibility to pneumonia [66]. Barns with a slatted floor are characterized by high concentrations of toxic gases, including ammonia, which also contribute to respiratory infections [13,67,68]. This observation could explain the higher prevalence of pneumonia in cows kept on a slatted floor.…”
Section: Discussionmentioning
confidence: 99%
“…It is difficult to accept the lack of basic freedom of movement in tie-stall systems [10,11]. Research has shown that selected technological solutions can improve animal welfare and decrease greenhouse or toxic gas emissions and microbiological contamination in buildings, which indirectly improves the health status and disease resistance of animals [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…One method of reducing GHG emissions is by improving or changing the housing system. It may result, depending on the type of animal, up to a 30% reduction of GHG emissions [23][24][25][26]. Another effective method is covering manure or slurry storage and closing the slurry channel, producing a 10% GHG reduction [27,28].…”
Section: Manure Managementmentioning
confidence: 99%